A gender analysis of forest products markets in Cameroon - Ruíz Pérez, M.; Ndoye, O.; Eyebe, A.; Ngono, D.L. (2002)
Gender roles and the potential to tap women's experiences are keys for African economic development. The paper illustrates this potential with a gender analysis of forest product markets in the humid forest zone of Cameroon by describing the functioning of the market and analysing male-female differences. The results confirm that gender is the main basis for differentiating size of business, product specialization, and market strategies among traders. Priorities to improve trade also show some male-female differences. At the same time, there are no consistent difference in profit margins between genders, indicating that trading efficiency is similar, and that, given the right conditions, women entrepreneurs can be as successful as men. The results also indicate that the gender gap could be closing among the younger generation entering the market.